2002
DOI: 10.1016/s0378-1097(02)01030-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the katA gene encoding a catalase and evidence for at least a second catalase activity in Staphylococcus xylosus, bacteria used in food fermentation

Abstract: The catalase gene katA of Staphylococcus xylosus was cloned. It encodes a protein of 494 amino acids with a molecular mass of 56.9 kDa, closely related to monofunctional catalases. A katA mutant still showed a relatively high catalase activity demonstrating that S. xylosus possesses more than one enzyme. By Southern blot analysis using a katA probe, a second genetic locus distinct from katA was detected that probably contained the additional catalase gene. To analyse katA expression, a transcriptional fusion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…Moreover, 23 of the 31 S. xylosus strains analyzed showed restriction profiles similar to that of DSM 20266 T (data not shown). The presence of a second kat gene (katB) in strain S. xylosus DSM 20266 T , similar to the one described by Barrière et al (3), was indicated by TaqI restriction digestion of the KDN-For/KDN-Rev PCR product, and the full nucleotide sequence (accession number AY702101) was determined by inverse PCR experiments, i.e., digesting total DNA with TaqI and using KBSxFI2 (CCTGACGAAGCAGCGAAAAT) and KBSxFI4 (ACGCGTTCACCTTTGTCGTT) as inverse primers in the PCR.…”
Section: Resultssupporting
confidence: 82%
“…Moreover, 23 of the 31 S. xylosus strains analyzed showed restriction profiles similar to that of DSM 20266 T (data not shown). The presence of a second kat gene (katB) in strain S. xylosus DSM 20266 T , similar to the one described by Barrière et al (3), was indicated by TaqI restriction digestion of the KDN-For/KDN-Rev PCR product, and the full nucleotide sequence (accession number AY702101) was determined by inverse PCR experiments, i.e., digesting total DNA with TaqI and using KBSxFI2 (CCTGACGAAGCAGCGAAAAT) and KBSxFI4 (ACGCGTTCACCTTTGTCGTT) as inverse primers in the PCR.…”
Section: Resultssupporting
confidence: 82%
“…The remaining culture was treated with 150 mM hydrogen peroxide (Sigma-Aldrich) and incubated for 1 h at 30°C. 4,000 U/mL of catalase (Sigma–Aldrich) was added to quench residual H 2 O 2 as described (Barrière et al, 2002). Cells were serial-diluted and plated in duplicate on TSA for enumeration of CFU from surviving cells.…”
Section: Methodsmentioning
confidence: 99%
“…The amino acid residues of the active site are very important in preservation of enzyme functions and much research revealed it was rather conserved in catalases [22,23]. According to the amino acid residues of bovine liver catalase site and alignment analysis of amino acid sequence, the active sites of the catalase from Serratia marcescens SYBC08 were consisted of H54, N127, and S93.…”
Section: Gene Cloning and Sequence Analysismentioning
confidence: 99%